2020
DOI: 10.3390/ma13132967
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Polyethylene Hybrid Composites with Natural Fiber: Mechanical, Thermal Properties, and Micromechanics

Abstract: The work assumed the possibility of the introduction natural fibers as a hybrid reinforcement of bio-polyethylene composites. Coconut fibers, basalt fibers and wood flour were used in different combination as a hybrid merger. Mechanical tests were conducted. An increase in the mechanical properties was shown as an effect of the introduction of the fibers info the polymeric matrix. A synergic influence of hybrid reinforcement was also presented. Experimental results were compared with modeling parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…The room temperature mechanical properties’ improvement correlates well with the results by other authors, who have reported basalt fiber reinforcement in the range of 25–40% [ 37 ]. Furthermore, the effect of the temperature on the composites has been discussed, but the morphologies of the samples in those works have been very different from those of ours, and thus the relevant conclusions cannot be transposed.…”
Section: Resultssupporting
confidence: 88%
“…The room temperature mechanical properties’ improvement correlates well with the results by other authors, who have reported basalt fiber reinforcement in the range of 25–40% [ 37 ]. Furthermore, the effect of the temperature on the composites has been discussed, but the morphologies of the samples in those works have been very different from those of ours, and thus the relevant conclusions cannot be transposed.…”
Section: Resultssupporting
confidence: 88%
“…A higher degree of crystallization results in higher mechanical properties, this relationship was also confirmed in this study. Another very important feature of polymeric materials is their water absorption and changes in properties triggered by the ageing process, which may include, e.g., self-stress relaxation, recrystallization, phase dispersion in multicomponent systems, softener migration, the formation of stress and fatigue cracks, thermo-oxidative degradation, or evaporation or migration of volatile components [47,48]. All these effects affect mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the development of composites with BioPE polymeric matrix is of great importance, due to the potential for technological application and the reduction of environmental impacts [18]. There are works in the literature on polyethylene composites reinforced with jute [19,20], curauá [21], sisal [22,23], coconut ber [24,25], cotton [26], rice husk [27] and wood powder [28,29], suggesting good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%